An Investigation into the Impact of Flexural Elastic Modulus on the Dimensional Instability in CNC Turning of Titanium Alloy Grade 5 - Ti6Al4V / Sangeeth Suresh...[et al.] - Suresh, Sangeeth; Abdul Hamid, Darulihsan; Yazid, MZA; Che Daud, Nur Rusydina; Mohd Din, Nik Nur Liyana (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Titanium Alloy Grade 5 (Ti6Al4V) has proven to be the most commonly used grade of titanium due to its excellent combination of physical and mechanical properties. However, Ti6Al4V has a relatively low modulus of elasticity (110 GPa) which in turn causes the material to be springy in nature. This springy nature of the material is a hindrance during the machining of Ti6Al4V as it may tend to push the workpiece away from the tool when the cutting force is applied. Actual dimensions are expected to change considerably from the intended dimensions due to this effect. This study attempts to investigate the magnitude of irregularity in the dimension during the CNC turning of Ti6Al4V (diameter 50mm) and the factors that significantly contribute towards the dimensional instability. The determinants of surface roughness and also the relationship between the dimensional instability and surface roughness are evaluated. Common machining parameters have been assigned as controlled and manipulated variables and an experimental design is formulated in order to record the responses through an actual standard experimental setup. It has been observed that the influence of its low elastic modulus, which is further aggravated by the depth of cut, and the generated cutting force contributes to between 25 - 40 % of residual stock on the diameter of a cylinder. The cutting force in turn significantly depends on the feed rate and the depth of cut. The higher the cutting force, the greater the deflection of the workpiece away from the cutting tool due to its flexural elastic modulus, thus causing the dimensional instability in the turning process. Regardless of the depth of cut and the cutting speed, a slower feed has proven to produce a finer surface finish on the workpiece. The surface finish is positively corelated to the cutting force. However, no specific relationship is observed between the surface finish and the tool wear. Also the surface finish and the dimensional instability show no mutual dependence.